DO TOURISTS AND LOCAL COMMUNITY HAVE THE SAME PERCEPTION OF TOURISM IMPACTS IN A RIVER BEACHES REGION? - Brito, Gleicon Queiroz de; Murta, Johnny Rodrigues de Melo; Silva, Thallia Santana; Carneiro, Adriana de Souza; Gomes, Gabriela dos Santos; Mendonça Filho, Sérgio Fernandes; Salemi, Luiz Felippe (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1133, 2021)
This study aimed to investigate the perception of tourists (TRs) and the local community (CL) about the positive and negative impacts of tourism in Cocalinho-MT, a city located on the middle course of the Araguaia River. We surveyed during the high season (July/2019) by applying a semi-structured questionnaire. Both the TRs and CL highlighted the positive economic impact of tourism. Concerning the negative impacts, both groups highlighted the environmental impact of tourism. The perception of tourism for TRs and CL pointed out impacts in the economic, social and environmental areas. Information like this can assist decision-makers in management strategies in the Cocalinho region and other similar tourist regions.